Papillon - Charriere, Henri frey50 (William Morrow and Company 1970, 1970)
Henri Charriere himself is Papillon. Convicted in Paris in 1931, aged 25, for a murder he had not committed, jCharriere was sentenced to life imprisonment in the penal colony of French Guiana. One thought obsessed him: escape. Forty-two days after his arrival in 1933, he made his first break, traveling on the open sea in a tiny boat. In desperate stages, 1500 miles in all, he reached Colombia. There he was recaptured by the French authorities and sentenced to two years in solitary confinement.